Ethosuximide-loaded bismuth ferrite nanoparticles as a potential drug delivery system for the treatment of epilepsy disease - Guldorum, Yeliz; Ayran, Musa; Bulut, Burcak; Ilgar, Sule; Ulag, Songul; Kanli, Zehra; Aydin, Banu; Gulhan, Rezzan; Bedir, Tuba; Gunduz, Oguzhan; Narayan, Roger J. (PUBLIC LIBRARY SCIENCE, 2024)
Encapsulating antiepileptic drugs (AEDs), including ethosuximide (Etho), into nanoparticles shows promise in treating epilepsy. Nanomedicine may be the most significant contributor to addressing this issue. It presents several advantages compared to traditional drug delivery methods and is currently a prominent area of focus in cancer research. Incorporating Etho into bismuth ferrite (BFO) nanoparticles within diverse controlled drug delivery systems is explored to enhance drug efficacy. This approach is primarily desired to aid in targeted drug delivery to the brain's deepest regions while limiting transplacental permeability, reducing fetal exposure, and mitigating associated adverse effects. In this investigation, we explored Etho, an antiepileptic drug commonly employed for treating absence seizures, as the active ingredient in BFO nanoparticles at varying concentrations (10 and 15 mg). Characterization of the drug-containing BFO nanoparticles involved scanning electron microscopy (SEM) and elemental analysis. The thermal properties of the drug-containing BFO nanoparticles were evaluated via differential scanning calorimetry (DSC) analysis. Cytotoxicity evaluations using the MTT assay were conducted on all nanoparticles, and human neuroblastoma cell line cultures (SH-SY5Y) were treated with each particle over multiple time intervals. Cell viability remained at 135% after 7 days when exposed to 15 mg of Etho in BFO nanoparticles. Additionally, in vitro drug release kinetics for Etho revealed sustained release lasting up to 5 hours with a drug concentration of 15 mg.
Keywords: BLOOD-BRAIN-BARRIER; CELL-ADHESION; SURFACE; BIOCOMPATIBILITY; TEMPERATURE; Science & Technology - Other Topics